The Holocaust, Fascism and Memory - Stone, D. author. aut Link
IX, 250 p.
Keywords: From interpretations of the Holocaust to fascist thought and anti-fascists' responses, this book tackles topics which are rarely studied in conjunction. This is a unique collection of essays on a wide variety of subjects, which contributes to understanding the roots and consequences of mid-twentieth-century Europe's great catastrophe.